Investigation into the ion channels and plasma membrane properties of white adipocytes - Bentley, Donna C. (2013)
Ca2+ is a ubiquitous intracellular signalling molecule that is involved in the regulation of numerous cellular functions. To date Ca2+ influx pathways present in white fat adipocytes have not been characterised. Additionally impaired [Ca2+]i management is implicated in the induction of the insulin resistant state in adipocytes. As adipocytes have a prominent role in the management of energy homeostasis, the presence of Ca2+ influx pathways was examined.